GRAPHIC MEETS AGRICULTURE: EXPLORING CROSS-INDUSTRY COLLABORATION FOR EFFECTIVE AGRO-PRODUCE PACKAGING IN NIGERIA - Ayodele, A. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Post-harvest losses and limited market competitiveness remain persistent challenges within the agricultural sector, particularly regarding the handling and packaging of agro-produce in Nigeria. While packaging is often treated as a logistical concern, its design and communicative dimensions play a critical role in value addition, product preservation, and consumer engagement. This study explores the intersection between graphic design and agriculture, positing that cross-industry collaboration can significantly enhance the functionality, appeal, and market reach of agro-produce packaging in Nigeria. Drawing on interdisciplinary literature and qualitative insights from stakeholders in both sectors, the research investigates the current state of agro-produce packaging, identifies key gaps in design application, and proposes a framework for integrating graphic design principles into agricultural packaging practices. The findings highlight the potential of design-driven innovation to transform Nigeria’s agro-processing and marketing landscape, with implications for economic development, export competitiveness, and sustainable agricultural practices.